Home Industry Powered Grid-Connected PV System an Economic Feasibility Study - Kartika Sri Kumala Sari; Wati Wati; Syafii Syafii (Electrical Engineering Dept, Engineering Faculty, Universitas Andalas, 2021)
This paper presents an analysis and feasibility of grid connected PV System for small scale home industry of welding workshop in Kambang Pesisir Selatan, Indonesia. The purpose of this paper is to analyze the feasibility of the on-grid PV system and obtain a comparison of the simulation results between the PV connected and only grid. The optimization results show that a feasible and optimal design configuration is a gid-connected PV system consisting of a Grid, PV system 3.48 kW, and a 5 kW inverter because it has a large intensity of solar radiation, which produces an economical generating system with a COE of Rp. 829/kWh, smaller than the basic cost of electricity provision that has been determined by the Ministry of Energy and Mineral Resources, which is IDR 1,058/kWh, in accordance with the criteria, the project is feasible to build.